Antiwear, Antifriction, and Extreme Pressure Properties of Motor Bike Engine Oil Dispersed with Molybdenum Disulfide Nanoparticles. Issue 1 (2nd January 2017) - Srinivas, V.; Thakur, R. N.; Jain, A. K.
ABSTRACT: This work presents studies on the antiwear, antifriction, and extreme pressure properties of motor oil dispersed with MoS2 nanoparticles. Commercial oil (SAE 20W-40 grade) is dispersed with stabilized MoS2 nanoparticles in 0.25, 0.5, 0.75, and 1 wt%. The test oils are tested for antiwear, antifriction, and extreme pressure properties on a four-ball wear tester. The wear and friction offered by nanolubricants has decreased remarkably compared to the commercial base oil. The weld load and load wear index of oils dispersed with nanoparticles were improved substantially compared to the commercial base oil. Metallographic studies conducted on the wear balls from the extreme pressure test show that nanoparticles are deposited on the worn area along with additives in the oil, thereby preventing welding of the surfaces. An optimum weight fraction is arrived at for best performance. A synergy between the additives in the oil and dispersed nanoparticles has been observed, resulting in less dispersion for best results. It is found that beyond an optimum weight percentage of nanoparticles, the trends tend to reverse, resulting in greater wear and friction.